A survey of NHS consultant pharmacists in england. Issue 2 (12th March 2012) - Howard, P.
Abstract : Background: Consultant pharmacist is a restricted title in the National Health Service (NHS). They were introduced in 2005 to provide best care for patients and to retain experienced pharmacists in clinical practice. The posts have four key functions: expert practice (max. 50%); research, evaluation and service development; education, mentoring and overview of practice; professional leadership. Purpose: The aim of the survey was to quantify for the first time the quantity and range of activities being undertaken by the NHS consultant pharmacists in England. Materials and methods: The survey built on a North West England survey of non-medical consultants in 2010 with additional information required added to the existing survey. All were e-mailed the link to the SurveyMonkey in March 2011. This software collected and assimilated the responses. Results: There are 41 consultant pharmacists (23 female). Average age at appointment was 40. 17 were appointed under transition arrangements and 25 new posts. There are currently no posts in Scotland, Northern Ireland or Wales. 68% work in acute teaching hospitals, 12% acute non-teaching, 5% in mental health, 7% in primary care and 5% in specialist trusts. The most common specialties are: 8 in critical care, 7 in antimicrobials / infectious disease / HIV, 5 in haemato-oncology, 4 paediatrics, 3 cardiology and 3 in medication safety. 73% work full time. On average 50% of time was in direct or indirect patient care, 15% leadership, 10% education, 10% research and 10% practice development. 36% run a clinic and 28% have their own caseload. 69% are prescribers. Two-thirds provide advice at a national level. Only 36% are formally linked to a university, but most are research active and published. 68% intended remaining in post. Conclusions: Consultant Pharmacists deliver the four key functions required by the post, and retain experienced pharmacists in clinical practice.